Biodiversidade no prato: inserção da Ora-pro-nobis (Pereskia aculeata mill) na alimentação escolar do município de Capitão Leônidas Marques-PR - Simonetti , Mariana Grisa (2021)
The support for sustainable development through the acquisition of foodstuffs through family farming in the National School Meals Program (PNAE) can be a gateway to Non-Conventional Food Plants. With a wide culinary application, the ora-pro-nobis (Pereskia aculeata Mill) is part of this group, has a high content of essential amino acids, dietary fiber, iron and carotenoids, and can contribute to the valorization of the Brazilian biodiversity, nutritional enrichment of the diet and incentive to family agriculture. The present work aimed at awakening the sensoriality of schoolchildren served by PNAE through the inclusion of ora-pro-nobis (Pereskia aculeata Mill) in recipes and dishes. This is an exploratory-descriptive research conducted with family farmers participating in the PNAE and students from 8 to 10 years old enrolled in a municipal school in Capitão Leônidas Marques - PR. The Food and Nutrition Education (EAN) was used to approach the non-conventional food plants in the school community, involving other social actors, namely: nutritionist, teachers, suppliers, cooks and students' parents. Sixteen family farmers and 57 schoolchildren participated in the research. The most mentioned preparation among the students was the omelet using the ora-pro-nobis (Pereskia aculeata Mill). Other species of non-conventional food plants were identified in the research, however, the lack of incentive to consumption and production compromises the transmission of knowledge linked to them, and this makes this cultural heritage subject to disappearance. However, the cultural rescue of eating habits represents a big step towards the transformation of hegemonic agri-food systems, improving the monotony of the diet and promoting food and nutritional security.